The cycle of frauds and conditions increasing their risk - Mackevičius, Jonas (Business: Theory and Practice, 2012)
The article presents the analysis of the main stages of fraud life cycle: intension, preparation, implementation, detection or not detection, estimation and prevention. The conditions of fraud appearance are various. The article explores the seven main groups of conditions that increase the fraud risk: 1) organization’s leaders competency and their management style; 2) staff and their skill levels; 3) organizational structure of enterprise; 4) financial state of the organization; 5) organization’s operations and execution; 6) accounting, auditing and internal control system; 7) external economic factors. This classification helps the leaders of organizations, accountants, internal and external auditors to find frauds easier, explain their reasons and evaluate their influence on business results.Article in Lithuanian.Apgaulių gyvavimo ciklas ir sąlygos, didinančios jų atsiradimo rizikąSantrauka. Straipsnyje nagrinėjamos svarbiausios apgaulių gyvavimo ciklo fazės: ketinimo, pasiruošimo, įvykdymo, aptikimo ar neaptikimo, įvertinimo ir prevencijos; daug dėmesio skiriama sąlygoms, kuriomis gali įvykti vienokio ar kitokio pobūdžio apgaulės. Visos sąlygos suskirstytos į septynias grupes, t. y. sąlygos, susijusios su: 1) įmonės vadovybės dora ir veiklos stiliumi; 2) įmonės darbuotojais; 3) organizacine įmonės struktūra; 4) finansine įmonės būkle; 5) įmonės veiklos organizavimu; 6) apskaita, auditu ir vidaus kontrolės sistema; 7) kitos. Ši klasifikacija padės įmonių vadovams, buhalteriams, auditoriams lengviau surasti apgaules, išaiškinti jų atsiradimo priežastis ir vietą, objektyviau įvertinti jų įtaką veiklos rezultatams.Reikšminiai žodžiai: klaida, apgaulė, gyvavimo ciklas, sąlygos, rizika, auditorius.